当X—>0时,f(X)=(1-cosx)ln(1+2X^2)与()是同阶无穷小量A.X^3B.X^4C.x^5D.X^2
当X—>0时,f(X)=(1-cosx)ln(1+2X^2)与()是同阶无穷小量A.X^3B.X^4C.x^5D.X^2
若集合A={x|-5<;x<;2},B={x|-3<;x<;3},则A∩B=( ) A: {x|-3<;x<;2} B: {x|-5<;x<;2} C: {x|-3<;x<;3} D: {x|-5<;x<;3}
若集合A={x|-5<;x<;2},B={x|-3<;x<;3},则A∩B=( ) A: {x|-3<;x<;2} B: {x|-5<;x<;2} C: {x|-3<;x<;3} D: {x|-5<;x<;3}
若集合A={x|-3<x<3},B={x|(x+4)(x-2)>0},则A∩B=( )A.{x|-3<x<2}B.{x|2<x<3}C.{x|-3<x<-2}D.{x|x<-4或x>-3}
若集合A={x|-3<x<3},B={x|(x+4)(x-2)>0},则A∩B=( )A.{x|-3<x<2}B.{x|2<x<3}C.{x|-3<x<-2}D.{x|x<-4或x>-3}
设函数$y = f({x^3})$可导,求函数的二阶导数$y'' = $( ) A: $6xf'({x^3}) + 9{x^4}f''({x^3})$ B: $6f'({x^3}) + 9{x^3}f''({x^3})$ C: $6xf'({x^3}) + 9{x^3}f''({x^3})$ D: $6{x^2}f'({x^3}) + 9{x^3}f''({x^3})$
设函数$y = f({x^3})$可导,求函数的二阶导数$y'' = $( ) A: $6xf'({x^3}) + 9{x^4}f''({x^3})$ B: $6f'({x^3}) + 9{x^3}f''({x^3})$ C: $6xf'({x^3}) + 9{x^3}f''({x^3})$ D: $6{x^2}f'({x^3}) + 9{x^3}f''({x^3})$
求微分方程[img=372x60]17da65376dc1787.jpg[/img]的通解。 ( ) A: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 B: C26*exp(3*x) + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 C: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 D: C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6
求微分方程[img=372x60]17da65376dc1787.jpg[/img]的通解。 ( ) A: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 B: C26*exp(3*x) + C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6 C: C26*exp(3*x) + (x*exp(3*x)*(x + 1)^2)/2 D: C27*x*exp(3*x) - (x^2*exp(3*x)*(2*x + 3))/6
设A={x∣x<-3},b={x∣x>3},则A∪B=
设A={x∣x<-3},b={x∣x>3},则A∪B=
A={x▏0<x≦2},B={x▏1<x≦3},则A∩B和A∪B分别是( ) A: {x▏1<x≦3}和{x▏0<x≦3} B: {x▏1<x<2}和{x▏2<x≦3} C: {x▏1<x≦2}和{x▏0<x≦3} D: {x▏1<x≦2}:和{x▏0<x<3}
A={x▏0<x≦2},B={x▏1<x≦3},则A∩B和A∪B分别是( ) A: {x▏1<x≦3}和{x▏0<x≦3} B: {x▏1<x<2}和{x▏2<x≦3} C: {x▏1<x≦2}和{x▏0<x≦3} D: {x▏1<x≦2}:和{x▏0<x<3}
下列语句正确的是________。 A: If X < 3 * Y And X > Y Then Y = X ^ 3 B: If X < 3 * Y And X > Y Then Y = X3 C: If X < 3 * Y : X > Y Then Y = X ^ 3 D: If X < 3 * Y And X > Y Then Y = X * * 3
下列语句正确的是________。 A: If X < 3 * Y And X > Y Then Y = X ^ 3 B: If X < 3 * Y And X > Y Then Y = X3 C: If X < 3 * Y : X > Y Then Y = X ^ 3 D: If X < 3 * Y And X > Y Then Y = X * * 3
下列语句正确的是( ) A: If x<3*y And x>y Then y=3x B: If x<3*y And x>y Then y=x^3 C: If x<3*y : x>y Then y=x^3 D: If x<3*y And x>y Then y=x**3
下列语句正确的是( ) A: If x<3*y And x>y Then y=3x B: If x<3*y And x>y Then y=x^3 C: If x<3*y : x>y Then y=x^3 D: If x<3*y And x>y Then y=x**3
不等式︱x-2︱>1的解集是 A: x>3或x<1 B: x>3或x<-3 C: 1<x<3 D: -3<x<3
不等式︱x-2︱>1的解集是 A: x>3或x<1 B: x>3或x<-3 C: 1<x<3 D: -3<x<3